ChinaVis Data Challenge from 2015 to 2017 - Ying ZHAO; Zhuo ZHANG; Xiaoru YUAN (网络与信息安全学报)
The evolution of the ChinaVis Data Challenge from its origin 2015 to 2017 was presented.Firstly,the background and organization of the Data Challenge were introduced.Then,the competition contents and statistical data of the three years were summarized.Finally,the future development of the Data Challenge was discussed.